2017
DOI: 10.1097/sle.0000000000000422
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Number of Intersections of Staple Lines and Anastomotic Leakage After the Use of a Double Stapling Technique in Laparoscopic Colorectal Surgery

Abstract: Purpose:Laparoscopic intracorporeal colorectal anastomosis with double stapling technique is difficult because of unsuitable cutting angle in narrow pelvic cavity. For reasons of tilted and long linear staple line of rectal stump, circular anastomotic plane can make multiple intersections. The present study was designed to assess whether multiple intersections after double stapling technique is the risk factor of anastomotic complication in laparoscopic colorectal surgery.Materials and Methods:In total, 128 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 34 publications
(41 reference statements)
1
26
0
Order By: Relevance
“…Thus, it seems likely that our surgical quality for anastomosis, with AL=6.8% during LAR and L -LAR, is adequate. Previous studies reported risk factors for AL such as anastomosis level 4) , tumor location 5 -8,16) , tumor size 9) , multiple stapler firings 4,8,10,16) , operation time 6,8) , intraoperative blood loss 11,12) , body mass index 7) , male gender 8,14) , and preoperative chemoradiotherapy 16) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems likely that our surgical quality for anastomosis, with AL=6.8% during LAR and L -LAR, is adequate. Previous studies reported risk factors for AL such as anastomosis level 4) , tumor location 5 -8,16) , tumor size 9) , multiple stapler firings 4,8,10,16) , operation time 6,8) , intraoperative blood loss 11,12) , body mass index 7) , male gender 8,14) , and preoperative chemoradiotherapy 16) .…”
Section: Discussionmentioning
confidence: 99%
“…13 In this technique, there were still some limitations that the future might be cut while enlarging the outlet using electrocautery to pull out the central rod of the anvil, as in the procedure reported by Omori et al, 18 and the double "over-line" of stapling might be a potential pitfall for anastomosis leakage and stenosis. 19,20 To address these problems or limitations, a simple and safe universal intraluminal poke technique was introduced, by which easy and common anvil placement at the stomach and intestine can be Follow-up, mo, median, range 6.5 (2.5-9)…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, our team introduced an anvil placement technique for the intracorporeal circular‐stapled gastrojejunostomy in which the needle attached to the central rod was pierced out in forehand approach under direct supervision, and only the suture was pulled out before closing the opening of the anvil insertion . In this technique, there were still some limitations that the future might be cut while enlarging the outlet using electrocautery to pull out the central rod of the anvil, as in the procedure reported by Omori et al, and the double “over‐line” of stapling might be a potential pitfall for anastomosis leakage and stenosis …”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, these techniques still have some disadvantages or limitations, such as the long delivery of the anvil inside the jejunal lumen and requirement of jejunal end or opening for anvil placement at the jejunum in the "intraluminal poke technique", 1 which is not applicable for delivering the anvil along longer intestinal segments or the complete intestine, and cumbersome approach involving an additional side-to-side jejunojejunostomy of the afferent loop segment or the double "over-line" crossing the anastomosis in the Billroth II reconstruction technique, 2 which may carry the risks of anastomotic leakage and stenosis. [3][4][5] Here, we first introduce an original, simple, easy, and safe technique in novel surgical concept and procedure for anvil placement: the u-shaped, parallel purse-string suture technique. This novel technique consists of merely four seromuscular stitches in two parallel unidirectional sutures along the jejunum with good reproducibility in a forehand style.…”
mentioning
confidence: 94%
“…To overcome these problems, we previously introduced two techniques for anvil placement in intracorporeal circular‐stapled jejunojejunostomy or gastrojejunostomy . However, these techniques still have some disadvantages or limitations, such as the long delivery of the anvil inside the jejunal lumen and requirement of jejunal end or opening for anvil placement at the jejunum in the “intraluminal poke technique”, which is not applicable for delivering the anvil along longer intestinal segments or the complete intestine, and cumbersome approach involving an additional side‐to‐side jejunojejunostomy of the afferent loop segment or the double “over‐line” crossing the anastomosis in the Billroth II reconstruction technique, which may carry the risks of anastomotic leakage and stenosis …”
Section: Introductionmentioning
confidence: 99%